2015
DOI: 10.1002/chin.201547224
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Symmetry‐Breaking Structural Phase Transitions in Spin Crossover Complexes

Abstract: Symmetry-Breaking Structural Phase Transitions in Spin Crossover Complexes -[49 refs.]. -(SHATRUK, M.; PHAN, H.; CHRISOSTOMO, B. A.; SULEIMENOVA, A.; Coord. Chem. Rev. 289-290 (2015) 62-73, http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The dynamics of the phase transition has been interpreted using a structural model built in a wide variety of long-range ordered patterns of HS and LS molecules. [75][76][77][78][79][80]70 Up to now, spin state transitions with up to eight more or less clearly identified steps have been reported. In most of the cases, the crystal structure has been solved for all the steps, allowing a clear description of the HS/LS supramolecular ordering.…”
Section: From Short-range Correlations To Long-range Ordering Of Molecular Spin Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of the phase transition has been interpreted using a structural model built in a wide variety of long-range ordered patterns of HS and LS molecules. [75][76][77][78][79][80]70 Up to now, spin state transitions with up to eight more or less clearly identified steps have been reported. In most of the cases, the crystal structure has been solved for all the steps, allowing a clear description of the HS/LS supramolecular ordering.…”
Section: From Short-range Correlations To Long-range Ordering Of Molecular Spin Statesmentioning
confidence: 99%
“…Ferroelastic crystals may be considered as a type of ferroic crystal which are the mechanical analogues of ferroelectrics and ferromagnetics. Many phase transitions in SCO systems involve symmetry breaking processes, as recently reviewed78 , only a few of these are true ferroelastic transitions, and the resulting ferroelastic domain pattern has rarely been studied in details. One of the most documented ferroelastic SCO compound is [Fe(ptz) 6 ].…”
mentioning
confidence: 99%
“…In the short range, the molecular packing and the elastic energy costs, related to important structural changes, can also be at the origin of elastic frustration (Watanabe et al, 2016;Paez-Espejo et al, 2016). It can generate stepwise conversions of the fraction of HS molecules HS with temperature, as recently discussed in recent reviews (Shatruk et al, 2015;Ortega-Villar et al, 2016). Structural studies of several Fe II systems have reported periodic and aperiodic long-range order of LS and HS states (Boinnard et al, 1994;Chernyshov et al, 2003;Huby et al, 2004;Reger et al, 2001;Money et al, 2007;Luan et al, 2015;Yamada et al, 2006;Sato et al, 2009;Bré fuel et al, 2009Bré fuel et al, , 2010Collet, Watanabe et al, 2012;Bonnet et al, 2008;Clements et al, 2016;Pillet et al, 2012).…”
Section: Introductionmentioning
confidence: 97%